Metal–organic framework hybrid-assisted formation of Co3O4/Co-Fe oxide double-shelled nanoboxes for enhanced oxygen evolution - Wang, Xiao (2019)
Rational design of complex metal–organic framework (MOF) hybrid precursors offers great opportunity to construct various functional nanostructures. Here, a novel MOF hybrid-assisted strategy to synthesize Co3O4/Co-Fe oxide double-shelled nanoboxes is reported. In the first step, zeolitic imidazolate framework-67 (ZIF-67, a Co-based MOF)/Co-Fe Prussian blue analogue (PBA) yolk–shell nanocubes are formed via a facile anion-exchange reaction between ZIF-67 nanocube precursors and [Fe(CN)6] 3− ions at room temperature. Subsequently, an annealing treatment is applied to prepare Co3O4/Co-Fe oxide double-shelled nanoboxes. Owing to the structural and compositional benefits, the as-derived Co3O4/Co-Fe oxide double-shelled nanoboxes exhibit enhanced electrocatalytic performance for oxygen evolution reaction in alkaline solution.